Negotiating the Democratic Paradox: Approaches Drawn From Governance Efforts on Yellowstone River - Horton, Cristi C.; Gilbertz, Susan J.; Hall, Damon M.; Peterson, Tarla Rai (Frontiers in Communication, 2019)
We analyze perspectives on watershed governance articulated by community leaders along the Yellowstone River (Montana, U. S. A.). These leaders framed watershed governance as a process of negotiating tensions between individual rights and equality for all, embracing diverse viewpoints while achieving broad policy agreement, and acknowledging the constant presence of change. We conducted informant directed interviews and used the theoretical perspective of Mouffe's democratic paradox to analyze the resulting discourse. Their discourse indicated a belief that negotiating tensions between individual liberty and group sovereignty was simultaneously obligatory and difficult. These civic officials struggled to develop a pluralistic democracy that could legitimize heterogeneous perspectives of watershed residents. Their version of pluralistic democracy offers one model for negotiating the democratic paradox that may be especially useful in environmental conflicts where property and other individual rights vie with egalitarian access to shared resources. Their leadership struggles offer lessons regarding ways to position all citizens who wish to effect change through participation in the democratic process.